Assessing Differences in Species Susceptibility to Phocine Distemper Virus (PDV) in Harp (Phoca groenlandica), Harbor (Phoca vitulina concolor) and Gray Seals (Halichoerus grypus) of the Northwest Atlantic - Bogomolni, Andrea (OpenCommons@UConn, 2014)
The recent emergence of morbillivirus in marine mammals as the etiology of several large scale mortality events raised questions about the role of immunosuppressive persistent organic pollutants and natural toxins in the severity, extent and duration of events. A morbillivirus of marine mammals, Phocine distemper virus (PDV), had devastating population level effects in Europe in 1988 and 2002. In 2006, a new isolate of PDV was determined to be responsible for mortality during the 2006 Northeast US Pinniped Unusually Mortality Event. The recent North American PDV mortality event provided a means to test several hypotheses designed to increase our overall understanding of different effects of PDV USA 2006 on harbor, harp and gray seals, and the relationship between PDV susceptibility and both natural and anthropogenic chemical stressors. The development of a sensitive duplex RT-qPCR assay utilizing the isolated North American strain, PDV USA 2006, allowed investigation into differences in species susceptibility in naturally infected as well as in-vitro infected host immune cells. In this study we demonstrated that species differences in susceptibility do exist in the quantity of virus produced during the course of infection. We also determined that differences in-vitro correlate with findings in seals naturally infected with PDV USA 2006. Furthermore, we described the effects of Aroclor 1260 on harbor seal peripheral blood mononuclear cell (PBMC) susceptibility in-vitro and show a disruption in the timing of the infection eventually resulting in more severe infection. In contrast, low levels of saxitoxin (STX) induced a transient increase in PDV replication during early infection and affected T cell proliferation. This is the first in-vitro exposure of immune cells of seals to STX to determine an immunomodulatory effect in a marine mammal, and this is the first documentation of an effect of exposure to STX and resultant change in quantity of morbillivirus after in-vitro exposure in harbor seal PBMCs. While it is ...